1946
DOI: 10.1021/ie50436a014
|View full text |Cite
|
Sign up to set email alerts
|

Vapor-Liquid Equilibria in Three Hydrogen-Paraffin Systems

Abstract: The cooperation of the operating and technical staff of the Western Sugar Refinery on plant tests is appreciated. Many persons in the laboratory of The Dicalite Company aided in these tests; to them thanks are extended for valuable assistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0
2

Year Published

1953
1953
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 4 publications
1
9
0
2
Order By: Relevance
“…Information is available concerning the vaporliquid equilibrium of three binary hydrogen-paraffin hydrocarbon systems at temperatures between 100°and 300°F. and at pressures up to 5000 pounds per square inch (5). Kay (8) determined the bubble point and dew point pressures and temperatures for three mixtures of hydrogen in a petroleum naphtha and found a marked minimum solubility with respect to changes in temperature.…”
Section: Littlementioning
confidence: 99%
“…Information is available concerning the vaporliquid equilibrium of three binary hydrogen-paraffin hydrocarbon systems at temperatures between 100°and 300°F. and at pressures up to 5000 pounds per square inch (5). Kay (8) determined the bubble point and dew point pressures and temperatures for three mixtures of hydrogen in a petroleum naphtha and found a marked minimum solubility with respect to changes in temperature.…”
Section: Littlementioning
confidence: 99%
“…Sattler (1940) measured the solubility of hydrogen in paraffinic, naphthenic and aromatic solvents and showed that it is a linear function of pressure up to 15.2 MPa. Dean and Tooke (1946) determined the solubility of hydrogen in various paraffinic compounds for temperatures from 3 1 1 to 422 K and pressures from 3.45 to 34.5 MPa. They reported an increase in the hydrogen solubility with temperature and pressure, but a decrease with the solvent molar mass.…”
mentioning
confidence: 99%
“…The methods available for determining gas-liquid equilibrium can be grouped into static or dynamic methods. In static methods, the gas-liquid mixture is stirred with an electric stirring motor (Katz and Hachmuth, 1937), rocking mechanism (Dean and Tooke, 1946;Akers et al, 1954). or a magnetic stirrer (Legret et a]., 1981) in a closed cell until pressure and temperature reach equilibrium values.…”
mentioning
confidence: 99%
“…En ésta, se observó que el peso molécular de la decalina fue el menor, en comparación a los otros dos solventes. Con base en los resultados anteriores, al disminuir la temperatura la solubilidad disminuyó, de acuerdo a varias publicaciones [78], [124]. Harrison et al [125] reportaron experimentalmente que al aumentar la presión a una temperatura constante, la fracción del hidrógeno en el líquido aumentó, de manera similar a lo obtenido en la presente investigación.…”
Section: Equilibrio Termodinámico Para El Sistema Hidrógeno-hidrocarburounclassified
“…Cabe mencionar que la constante de Henry para el hidrógeno se obtuvo mediante el programa Aspen Plus mediante la simulación en un flash líquido-vapor (L-V), se consideraron las fracciones en equilibrio del L y V en equilibrio de salida. Otra manera de obtener esta constante es mediante el uso de ecuaciones de estado y con datos experimentales, como lo reportan Moysan et al [109] y Dean y Tooke [110].…”
unclassified